The use of omics technologies in creating LBP and postbiotics based on the Limosilactobacillus fermentum U-21 - Odorskaya, Maya V.; Mavletova, Dilara A.; Nesterov, Andrey A.; Tikhonova, Olga V.; Soloveva, Natalia A.; Reznikova, Diana A.; Galanova, Olesya O.; Vatlin, Aleksey A.; Slynko, Nikolai M.; Vasilieva, Asya R.; Peltek, Sergey E.; Danilenko, Valery N. (Frontiers in Microbiology, 2024)
In recent years, there has been an increasing tendency to create drugs based on certain commensal bacteria of the human microbiota and their ingredients, primarily focusing on live biotherapeutics (LBPs) and postbiotics. The creation of such drugs, termed pharmacobiotics, necessitates an understanding of their mechanisms of action and the identification of pharmacologically active ingredients that determine their target properties. Typically, these are complexes of biologically active substances synthesized by specific strains, promoted as LBPs or postbiotics (including vesicles): proteins, enzymes, low molecular weight metabolites, small RNAs, etc. This study employs omics technologies, including genomics, proteomics, and metabolomics, to explore the potential of Limosilactobacillus fermentum U-21 for innovative LBP and postbiotic formulations targeting neuroinflammatory processes.Proteomic techniques identified and quantified proteins expressed by L. fermentum U-21, highlighting their functional attributes and potential applications. Key identified proteins include ATPdependent Clp protease (ClpL), chaperone protein DnaK, protein GrpE, thioredoxin reductase, LysM peptidoglycan-binding domain-containing protein, and NlpC/P60 domain-containing protein, which have roles in disaggregase, antioxidant, and immunomodulatory activities. Metabolomic analysis provided insights into small-molecule metabolites produced during fermentation, revealing compounds with anti-neuroinflammatory activity. Significant metabolites produced by L. fermentum U-21 include GABA (γ-aminobutyric acid), niacin, aucubin, and scyllo-inositol. GABA was found to stabilize neuronal activity, potentially counteracting neurodegenerative processes. Niacin, essential for optimal nervous system function, was detected in vesicles and culture fluid, and it modulates cytokine production, maintaining immune homeostasis. Aucubin, an iridoid glycoside usually secreted by plants, was identified as having antioxidant properties, addressing issues of bioavailability for therapeutic use. Scyllo-inositol, identified in vesicles, acts as a chemical chaperone, reducing abnormal protein clumps linked to neurodegenerative diseases.These findings demonstrate the capability of L. fermentum U-21 to produce bioactive substances that could be harnessed in the development of pharmacobiotics for neurodegenerative diseases, contributing to their immunomodulatory, anti-neuroinflammatory, and neuromodulatory activities.Data of the HPLC-MS/MS analysis are available via ProteomeXchange with identifier PXD050857.